Letter from Max Bredig to Fritz Boas, December 1937 - Bredig, Max Albert (1937)
Max Albert Bredig (1902-1977) asks Fritz Boas about the sale of his motorcycle.
Keywords: Bredig, Max Albert, 1902-1977; Motorcycles; Boas, Fritz